Perampanel: first‐in‐class AED for partial‐onset seizures. Issue 6 (21st March 2013) - Chaplin, Steve; Kelso, Andrew
Abstract Perampanel (Fycompa), an AMPA receptor antagonist, is licensed as adjunctive treatment of partial‐onset seizures. In our New products review, Steve Chaplin presents the clinical data relating to its efficacy and adverse events and Dr Andrew Kelso discusses its place in the treatment of epilepsy.